The Impact of Work Motivation and Work Environment on Employee Performance in Organizational Contexts - Salman Alfarissy; Rifki Suwaji (PT Mattawang Mediatama Solution, 2025)
This study examines the influence of work motivation and work environment on employee performance within organizational contexts. The research focuses on CV Elsa Cahya in Gresik, involving all 30 employees as respondents through a saturated sampling technique. A quantitative approach was adopted, and data were gathered using structured questionnaires, interviews, and observations. Statistical analysis was performed using SPSS, which included descriptive analysis, instrument validity and reliability testing, classical assumption tests, and multiple linear regression analysis. The results show that both work motivation and work environment positively affect employee performance. However, only the work environment variable was statistically significant in the partial test, with a standardized beta coefficient of 0.827, making it the dominant factor compared to work motivation. The F-test indicates that the combination of both variables significantly explains 78.5% of the variance in employee performance. The regression analysis reveals that improvements in the work environment yield greater gains in performance compared to work motivation alone. The findings of this study suggest that the quality of the work environment plays a crucial role in enhancing employee productivity, making it a key consideration for organizational development and human resource strategies.